An Early Portuguese Mariner's Astrolabe from the Sodré Wreck‐site, Al Hallaniyah, Oman. (1st September 2019) - Mearns, David L.; Warnett, Jason M.; Williams, Mark A.
Abstract: A unique leaded‐gunmetal disc decorated with iconic Portuguese markings was recovered in 2014 during archaeological excavations at the Sodré shipwreck site in Al Hallaniyah, Oman. Initially the identity and function of the disc was unknown, although it did possess characteristics suggesting it could be an astrolabe. Laser imaging of the disc post conservation revealed regular scale marks on the limb of its upper right quadrant. Accurate digital measurements of the marks show them to be graded at close to 5‐degree intervals, thus confirming the identity of the disc as a mariner's astrolabe and the earliest known example discovered to date.